PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP PROBABILITAS FINANCIAL DISTRESS DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN NON EUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2016 - Faiza Sakinah; Haryetti Haryetti; Ahmad Fauzan Fathoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research is motivated by a number of companies that are experiencing financial distress which is marked by the delisted of the company from Indonesian Stock Exchange. This study aims to analyze the effect of liquidity and leverage to financial distress moderated by good corporate governance. The population in this study is non-financial companies listed in Indonesian Stock Exchange in 2014-2016 periods. The research samples are 262 companies which have been selected by using purposive sampling method. In this study used logistic regression model and descriptive statistics for the analysis of the data with the help of the program Eviews 10.0. The results shows that liquidity have a positive and not significant effect on financial distress. While on leverage and good corporate governance had a negative and significant effect on financial distress. Good corporate governance are able moderated the influence of leverage and financial distress. But, Good corporate governance is not able moderated influence between liquidity and financial distress.Keywords : financial distress, liquidity, leverage, and good corporate governance